Antibiotic stewardship for reptiles - Hedley, Joanna; Whitehead, Martin; Munns, Clive; Pellett, Sarah; Abou-Zahr, Tariq; Calvo-Carrasco, Daniel (Journal of Small Animal Practice, 2021)
This review discusses the general principles underlying responsible antibiotic usage in reptiles. Very little evidence underlies antibiotic usage in reptiles, and there are no published guidelines for responsible antibiotic usage. A literature search was performed to review the evidence for bacterial involvement in the pathology of selected common diseases of reptiles, allowing the development of recommendations for responsible antibiotic treatment of those diseases.